Drug-induced cutaneous vasculitis developing during Etanercept treatment for rheumatoid arthritis - Maria N. Chamurlieva (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Biological disease-modifying anti-rheumatic drugs (bDMARDs) are widely used for the treatment of chronic inflammatory rheumatic diseases. Since the introduction of tumor necrosis factor alpha (TNF-) inhibitors, the treatment of rheumatoid arthritis has been revolutionized. The approach of targeting TNF- has considerably improved the success of the treatment of rheumatoid arthritis. Their effectiveness has been extensively proven in randomized clinical trials and in clinical practice. Randomized clinical trials and post-marketing studies proved that patients undergoing TNF- inhibitors therapy are at increased risk of infectious disease, bacterial, viral, fungal, opportunistic, oncology and skin adverse effects such as psoriasis and angiitis of the skin. In this case report drug-induced cutaneous vasculitis developing during TNF- inhibitor (Etanercept) treatment for rheumatoid arthritis is described.